2021
DOI: 10.2174/1570162x18666200824101838
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Impact on Lipid Profile of a Switch from Tenofovir Disoproxil Fumarate to Tenofovir Alafenamide in HIV-Infected Patients

Abstract: Background: Tenofovir disoproxil fumarate is a prodrug of tenofovir diphosphate that exposes patients to renal toxicity over the long term. Tenofovir alafenamide, a new prodrug, now makes it possible to reduce toxicity, but at the cost of an alteration in lipid profile. There is currently no recommendation for follow-up of lipid profile when switching from tenofovir disoproxil fumarate to tenofovir alafenamide. Objective: Our study aimed to evaluate the effects on renal function and lipid profile of a swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Consistent with these previous reports, in our study, cholesterol levels decreased significantly during TDF administration ( Fig 2B ). However, other reports have shown that switching from TDF to TAF increased levels of cholesterols, including T-chol, LDL-c, and HDL-c, in patients with HIV infection [ 16 , 30 , 31 ]. As HDL-c and LDL-c have opposite effects on the development of atherosclerosis, the effects of changing both serum parameters are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these previous reports, in our study, cholesterol levels decreased significantly during TDF administration ( Fig 2B ). However, other reports have shown that switching from TDF to TAF increased levels of cholesterols, including T-chol, LDL-c, and HDL-c, in patients with HIV infection [ 16 , 30 , 31 ]. As HDL-c and LDL-c have opposite effects on the development of atherosclerosis, the effects of changing both serum parameters are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…These results enlighten the potential role of inflammation/oxidative stress as drivers for dyslipidemia, in addition to ART and individual factors. The different effect on lipids of TAF vs TDF, previously identified in clinical trials, was confirmed in the real life setting in several studies: switching TDF to TAF increased TC, LDL-C, HDL-C and TG while the LDL-C/HDL-C ratio remained stable (44,45). When TAF was switched back to TDF, lipid levels returned to previous values (46).…”
Section: -2 Mechanismsmentioning
confidence: 63%
“…Even though newer antiretrovirals do not elevate circulating lipids to the same extent, tenofovir prodrugs, including tenofovir alafenamide, increase cholesterol species (91). This occurs despite the known impact of HIV on diminishing total cholesterol levels (86,(92)(93)(94)(95). Conversely other ARTs, including raltegravir, dolutegravir, and bictegravir, have either a beneficial or minimal impact on the cholesterol profile (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%